Mesenchymal stem cell-mediated immunomodulation of microglia - Jose, Shinsmon (2013)
Neuroinflammation is a key pathogenic event of neurological diseases. The continuous inflammatory responses of microglia exacerbate disease by increasing neuronal damage, an effect that may warrant control. An approach for this is the utilisation of mesenchymal stem cells (MSC). This study explores the mechanisms through which MSC modulate inflammatory responses of microglia. For this, mouse bone marrowderived MSC and BV2 (a microglial cell line) were cocultured at different ratios. The anti-proliferative effect of MSC on microglia was deciphered by examining cell cycle, apoptosis and the role of nitric oxide (NO). Migration of both cell types was also examined along with differential expression of soluble mediators. Direct contact of BV2 with MSC at the 1:0.2 (BV2:MSC) seeding ratio inhibited proliferation of LPS-stimulated BV2 microglia to 71.2 ± 9.7% (p<0.05), an effect also conferred by MSC soluble factors. At the same 1:0.2 ratio, MSC also increased NO expression in cocultures, inducing a 25% surge from 56.94 ± 2.65μM to 76.59 ± 3.08μM at 48hrs (p<0.05). However, NO was not implicated in the anti-proliferative effect as inhibiting NO did not restore BV2 proliferation. Role of apoptosis in the reduction of BV2 proliferation was also ruled out as the number of Annexin-V-/PI- cells remained high. A slowdown of cell cycle was identified as the mechanism through which MSC exert their anti-proliferative effect on microglia. Coculture with MSC reduced the population of BV2 microglia in S-phase by 6.25 ± 1.5% (p<0.001) and restored the percentage of BV2 cells at the G2/Mphase to levels similar in unstimulated BV2 microglia. The immunomodulatory effects reported here were also accompanied by an MSC cell cycle arrest at G0/G1-phase (percentage of MSC in G0/G1-phase increased from 55.34 ± 2.6% to 86.32 ± 2.0% (p<0.001)). Using protein array, galectin-1 was identified as a possible immunomodulator as its levels increased significantly to 2.16-fold in coculture (p<0.05). Presence of MSC also increased IL-6 (by 30-fold, p<0.05) whereas TNF-α was reduced by 4-fold (p<0.05). The study then explored the role of IL-6 and TNF-α in MSC-mediated modulation of NO production and proliferation of microglia. By using neutralising antibodies, it was shown that IL-6 did not play a role in the NO production of cocultures or inhibition of microglial proliferation, whilst neutralisation of TNF-α abolished the NO surge although leaving proliferation unaffected in coculture. As blocking TNF-α reduced LPS-stimulated BV2 proliferation, proliferation of microglia was proposed to be mediated by TNF-α and that MSC inhibit microglial proliferation by downregulating TNF-α levels in coculture. This study then pursued the migratory properties of microglia and MSC. The results demonstrated that BV2 cells showed remarkable migration to MSC, paralleled by an increase in MMP-9 activity (12.35 ± 2.89-fold). It was also shown that MSC intrinsically migrated towards microglia (208.5 ± 10.6), and more so in inflammatory conditions (295.3 ± 43.8). MSC also migrated towards LPS-stimulated astrocytes. However, LPS alone did not influence MSC migration,indicating the importance of a cellular impetus that MSC requires for their migration and the reciprocity in migration of BV2 microglia and MSC. The findings from this study shed light on mechanisms of immunomodulatory functions of MSC on microglia which improve our understanding for MSC-mediated therapy of neuroinflammatory conditions.